Exploring the relationship between web presence and web usability for universities: A case study from Turkey. Issue 2 (4th April 2016) - Peker, Serhat; Kucukozer-Cavdar, Seyma; Cagiltay, Kursat
Abstract : Purpose: – The purpose of this paper is to statistically explore the relationship between web usability and web presence of the universities. As a case study, five Turkish universities in different rankings which were selected from Webometrics rankings were evaluated and compared. Design/methodology/approach: – Two different methods were employed for performing usability evaluation of the selected universities: a user testing was used to measure the user performance on the selected tasks and a questionnaire to assess the user satisfaction on the website use. Both usability evaluation methods were applied on the pre-determined tasks for each university by participation of 20 subjects. After the usability evaluation, the universities were ranked in terms of usability results and finally, the relationship between web usability and web presence of universities was statistically investigated by using Kendall's rank correlation. Findings: – Several common usability problems which were asserted by related previous studies were identified at the end of usability evaluation of university websites. The usability results also revealed that selected Turkish university websites suffer from numerous usability problems. Further, a strong positive correlation ( p < 0.05) between the usability of the university websites and their web presences were identified. Hence, the participants showed a higher success and satisfaction while performing the tasks on the university websites which have strong web presences. Practical implications: – The findings from this study have practical implications for universities. Correlation results showed that universities can improve their web usability by giving importance to their web presence volumes. Universities can estimate their web usability levels by investigating their web presence rankings and they can also raise their rankings in Webometrics ranking system by improving the usability of their websites. Moreover, university web developers can design more usable and more user-friendly websites by avoiding usability and design problems identified through usability evaluation. Originality/value: – Different from the prior research efforts focussing on usability of educational web pages, this study contributes to the growing literature by statistically exploring the relationship between web presence and web usability of universities. This study is also precious from the point of view that it is one of the first attempts to evaluate and compare usability levels of a set of universities' websites from Turkey.